DENSITY AND DISTRIBUTION PATTERN OF KEPAH (Polymesoda spp) IN MANGROVE FORESTS OF MENDALOK VILLAGE SUNGAI KUNYIT SUB DISTRICTS MEMPAWAH REGENCY - LIA WATI; AHMAD MULYADI SIROJUL; INPURWANTO M.SI (Jurnal Sains Pertanian Equator, 2019)
ABSTRACTThis study aims to determine the density and pattern of distribution of kepah (Polymesoda spp) in the mangrove forest of Mendalok village. The sampling study used the method of sweeping with excavation (MSDG). To determine the location of sampling using purposive random sampling method that is how to collect samples from members of the population randomly by selecting the regions that tepresent the location of the study. The research area was divided into 3 stations, namely station I zone mangrove Rhizophora, station II zone mangrove Bruguiera and station III zone mangrove Nypah. The distance between stations was 50 m2. Earch station is divided into 3 transect lines with a distance of 10 m2 and each transect line consists of 8 plots with a distance of 10 m2. Sampling of mussels was carried out one time during the study. Substrate retrieval and measurement of environmental parameters such as temperature, pH, and salinity were carried out at each station two times during the study. This research was conducted in September-November 2018. The populasin of kepah in this study location is classified as very low, with Polymesda erosa densities ranging from 0.25-1.83 individual/m², the density of Polymesoda expansa ranges from 0.13-0.25 individual/m². The distribution pattern in the location of this study as a whole is clustered on this matter, as indicated by the morisita (id) index value of Polyesoda erosa 1.74 and Polymesoda expansa 1.72 greater than 1(>1), which means the distribution pattern is clustered.Keywords : Density, Distribution pattern, Kepah shells